Design of a Short-To-Medium-Range Baseline Aircraft with an Entry into Service in 2035 for the HOPE Project - Barlas Türkyilmaz; Michael Lüdemann; Moritz Georg Kolb; Alexandros Lessis (Aerospace, 2025)
When assessing new technologies at the overall aircraft level, it is crucial to establish an appropriate benchmark to evaluate the resulting performance of the final concept aircraft. This publication defines a short-to medium-range baseline aircraft for entry into service in 2035, which serves as a benchmark for the HOPE project. This aircraft is sized using the Bauhaus Luftfahrt Aircraft Design Environment (BLADE), and its engine model is derived using the in-house tool Aircraft Propulsion System Simulation (APSS). The top-level aircraft requirements and technology assumptions for the entire project timeline are also defined and used for the baseline aircraft. Compared to a state-of-the-art aircraft (entry into service in 2015), the baseline aircraft consumes 21.4% less block fuel during the design mission and 20.9% less block fuel during the typical mission, since its operating empty mass is reduced by 13.6%, its aerodynamic performance is improved by 8.5%, and it has 6.4% more efficient engines.